Springtime reactive volatile organic compounds (VOCs) and impacts on ozone in urban areas of Yunnan-Guizhou plateau, China: A PTR-TOF-MS study - Qing Li; Yan Han; Dasheng Huang; Jiawei Zhou; Hanxiong Che; Liuyi Zhang; Lu, Keding; Yang, Fumo; Yang Chen (Atmospheric Environment, 2023)
Field observations of reactive volatile organic compounds (VOCs) were carried out in Kunming, the largest city on the Yunnan-Guizhou Plateau. Proton transfer reaction-time-of-flight mass spectrometry (PTR-TOF-MS) was used to conduct a 40-day online observation. VOCs were characterized, including concentrations, diurnal variations, ozone generation potential, and source apportionment. The results show 18 main observed active VOCs (acetaldehyde, 2-acrolein, acetone, methyl ethyl ketone (MEK), methyl vinyl ketone (MVK), methacrolein (MACR), methyl isobutyl ketone (MIK), 2-pentanone, ethyl acetate, isoprene, α-pinene, benzene, toluene, styrene, C8 aromatic hydrocarbons, C9 aromatic hydrocarbons, 1,3-dichlorobenzene, naphthalene and acetonitrile) with a total concentration of (10.97 ± 5.21) ppb. Eight OVOCs have a total concentration of (7.49 ± 3.10) ppb; two biogenic VOCs (BVOCs) have a total concentration of (1.32 ± 0.79) ppb, and six aromatic hydrocarbons have a total concentration of (1.50 ± 1.14) ppb. The ozone formation potential of isoprene, acetaldehyde and 2-acrolein make up the top three species. The main sources of three OVOC species (acetaldehyde, acetone, and MEK) have local biological sources and primary anthropogenic sources, indicating that the pollution in this area is significantly affected by regional transport. This study can improve our scientific understanding of the composition and sources of VOCs on the Yunnan-Guizhou Plateau and fundamental ozone control in the region.
Keywords: Ozone formation potential; Photochemical age-based parameterization method; Proton transfer reaction-mass spectrometry (PTR-TOF-MS); source apportionment; Volatile organic compounds (VOCs)